Observed secular gravity trend at Onsala station with the FG5 gravimeter from Hannover. - Timmen, Ludger; Engfeldt, Andreas; Scherneck, Hans-Georg (Journal of Geodetic Science, 2015)
Annual absolute gravity measurements with aFG5 instrument were performed in Onsala Space Observatoryby the Institute of Geodesy of the Leibniz UniversitätHannover from 2003 to 2011 and have been continued withthe upgraded meter FG5X in 2014. Lantmäteriet, Gävle,with their FG5 absolute gravimeter have visited Onsalasince 2007. Because small systematic errors may be inherentin each absolute gravimeter, their measuring level anda resulting bias (offset) between the instruments must becontrolled over time by means of inter-comparison. From2007 to 2014, 8 direct comparisons took place well distributedover the time span. A complete re-processing ofthe absolute gravity observations with the Hannover instrumenthas been conducted to improve the reduction ofunwanted gravity effects. A new tidal model is based oncontinuous time series recorded with the GWR superconductinggravimeter at Onsala since 2009. The loading effectof the Kattegat is described with a varying sea bottompressure (water and air mass load) and has been validated with the continuous gravity measurements. For theland uplift,which is a result of the still ongoing glacial isostaticadjustment in Fennoscandia, a secular gravity trendof −0.22 μGal/yr was obtained with a standard deviationof 0.17 μGal/yr. That indicates a slight uplift but is still notsignificantly different from zero.